Radiological Assessment of Giant Cell Tumour of Bone in the Sacrum: From Diagnosis to Treatment Response Evaluation - Langevelde, Kirsten v.; Vucht, Niels Van; Tsukamoto, Shinji; Mavrogenis, Andreas F.; Errani, Costantino (Current Medical Imaging, 2022)
Giant cell tumour of bone (GCTB) typically occurs in young adults from 20-40 years old. Although the majority of lesions are located in the epi-metaphyses of the long bones, approximately one third of tumours are located in the axial skeleton, of which only 4% in the sacrum. Sacral tumours tend to be large at the time of presentation, and they present with aggressive features such as marked cortical destruction and an associated soft tissue component. The 2020 World Health Organisation classification of Soft Tissue and Bone Tumours describes GCTB as a neoplasm which is locally aggressive and rarely metastasizing. The tumour contains three different cell types: neoplastic mononuclear stromal cells, macrophages and osteoclast-like giant cells. Two tumour subtypes were defined: conventional GCTB and malignant GCTB. Only 1-4% of GCTB is malignant. In this review article, we will discuss imaging findings at the time of diagnosis to guide the musculoskeletal radiologist in reporting these tumours. In addition, imaging for response evaluation after various treatment options will be addressed, such as surgery, radiotherapy, embolization and denosumab. Specific findings will be presented per imaging modality and illustrated by cases from our tertiary sarcoma referral center. Common postoperative and post-radiotherapy findings in GCTB of the sacrum on MRI will be discussed.
Keywords: imaging